Lithium evolution in the low-mass evolved stars with asteroseismology and LAMOST spectroscopy - Hong-Liang Yan; Jing-Hua Zhang; Yu-Tao Zhou; Qi Gao; Jian-Rong Shi; Yerra Bharat Kumar; Wako Aoki; Haining Li; Chunqian Li; Gang Zhao (Fundamental Research)
Lithium is an ancient element that was first produced by the Big Bang Nucleosynthesis (BBN) a few minutes after the birth of the Universe. Lithium is a sensitive tracer for a number of processes in a variety of astrophysical environments due to its multi-channels of production and fragility. These features also make lithium a complex element at the center of many unsolved problems. The behavior of lithium in the low-mass evolved stars is one such issue. It is known that such stars not only destroy but also produce lithium, while neither the destruction details nor the production mechanisms over different evolutionary phases are clear. In this paper, we summarize the recent results obtained from the studies combining large-scale spectroscopic surveys, asteroseismology, and traditional high-resolution spectroscopy. We present the detailed evolution behaviors from the red giant branch (RGB) to the red clump (RC) phase characterized by the core helium-burning in the stellar interior. We show the new signatures discovered from the recent studies for the lithium-enhanced giants and also discuss various observational and theoretical constraints on lithium production in red clump stars.